Readiness for contingency: punctuation, poise, and co-design. Issue 1 (2nd January 2020) - Akama, Yoko; Light, Ann
ABSTRACT: How do we ready ourselves to intervene responsively in the contingent situations that arise in co-designing to make change? How do we attune to group dynamics and respond ethically to unpredictable developments when working with 'community'? This paper challenges co-design conventions that focus too tightly on formal process by addressing what happens at the moment when we step into situations to alter them with others. This is intrinsically relational and we expose the politics of practice that cannot be replicated or interchanged. Instead, we suggest that practices of readying are constituted by personal histories, experiences, philosophies, and cultures and demonstrate this by giving reflexive accounts of our dimensions of preparation. We have organised these accounts around the qualities of punctuation and poise as a way to draw out some less easily articulated aspects of co-design practice. These narratives are distinct, yet reveal complementary theories and worldviews that shape ontologies and, in turn, shape the experience – and politics – of collaboration.